Pengaruh Pendidikan Akhlak Terhadap Hubungan Bertetangga Harmonis - Asrokhi, Ahmad Khoiruddin; As’ad, Ali (Medan Resource Center, 2023)
Morals are traits that grow in human nature. These properties unite within themselves, thus becoming everyday life. Based on these morals, it is hoped that people can apply them in their daily lives in the form of morality towards God SWT, morality towards Rasulullah SAW, morality towards oneself, morality towards family, morality towards society and morality for the environment. The purpose of making this article is to be a guide for the community how to behave in society and uphold Islamic religious values, this is considered very important when considering many phenomena and cases, understanding and awareness of citizens that they must have morals for whatever happens. Actions responsible for the welfare and development of the country are reduced. Modernization and rapid globalization have contributed to the weakening of public awareness and apart from ethnic unity, our nation is a nation that is very diverse in all respect religion, race, ethnicity, culture and between groups.